The Korean Wave and Cultural Soft Power Diplomacy: Evaluating Its Impact on South Korea-Indonesia Bilateral Relations in the Creative Industries - Zahara, Bintang Radhityo; Ramadhan, Syifa Alim; Syabina, Siti Viesta Ramadanty; Milady, Thariq Kemal (Candidate: Jurnal Sains Politik, 2023)
This study explores the impact of the Korean Wave on the bilateral relations between South Korea and Indonesia, particularly in the creative industry sector. Using a descriptive qualitative approach, data were collected from various primary and secondary sources, including articles, blogs and social media. The results indicate that the Korean Wave has successfully enhanced South Korea's image in the eyes of the Indonesian public, increasing interest in Korean language, fashion, and cuisine. Furthermore, this phenomenon has driven the growth of the creative economy in Indonesia by increasing the demand for Korean products and creating new business opportunities. The cultural diplomacy strategy implemented by South Korea through the Korean Wave has proven effective in strengthening diplomatic relations between the two countries, opening up broader collaboration opportunities, and enhancing understanding and appreciation of Korean culture in Indonesia. Â 